Levels and risks of surface contamination by thirteen antineoplastic drugs in the Czech and Slovak hospitals and pharmacies - Doležalová, Lenka; Bláhová, Lucie; Kuta, Jan; Hojdarová, Tereza; Kozáková, Šárka; Bláha, Luděk (Environmental science and pollution research international, 2022)
The consumption of hazardous antineoplastic drugs (ADs) used in anticancer chemotherapies is steadily increasing representing thus risks to both human health and the environment. Hospitals may serve as a contamination source, and pharmacists preparing the antineoplastic drugs (ADs) as well as nurses administering chemotherapy and caring for oncology patients are among the healthcare professionals being highly exposed. Here, we present the results of systematic monitoring (2018-2020) of surface contamination by 13 ADs in the pharmacies and hospitals in the Czech Republic (CZ; large-scale monitoring, 20 workplaces) and Slovak Republic (SK; pilot study at 4 workplaces). The study evaluated contamination by three commonly monitored ADs, i.e., 5-fluorouracil (FU), cyclophosphamide (CP), and platinum (total Pt representing cis-, carbo-, and oxaliplatin) together with ten less explored ADs, i.e., gemcitabine (GEM), ifosfamide (IF), paclitaxel (PX), irinotecan (IRI), docetaxel (DOC), methotrexate (MET), etoposide (ETOP), capecitabine (CAP), imatinib (IMAT), and doxorubicin (DOX). Floors and desktop surfaces in hospitals (chemotherapy application rooms, nurse working areas) were found to be more contaminated, namely with CP and Pt, in both countries when compared to pharmacies. Comparison between the countries showed that hospital surfaces in SK are generally more contaminated (e.g., CP median was 20 times higher in SK), while some pharmacy areas in the CZ were more contamined in comparison with SK. The newly studied ADs were detected at lower concentrations in comparison to FU, CP, and Pt, but some markers (GEM, IF, PX, and IRI) were frequently observed, and adding these compounds to routine monitoring is recommended.
Keywords: Hospitals; Cyclophosphamide; nemocnice; Fluorouracil; monitorování životního prostředí; kontaminace zdravotnického vybavení; Equipment Contamination; Slovakia; lidé; Occupational Exposure; Antineoplastic Agents; Pilot Projects; protinádorové látky; pilotní projekty; ifosfamid; fluoruracil; pracovní expozice; Czech Republic; Pharmacies; Environmental Monitoring; Česká republika; Ifosfamide; Slovenská republika; lékárny; cyklofosfamid; Humans